Ultrasonically Deposited Boron‐Doped Silicon Decorated with Laser‐Generated Iridium Nanoparticles as Manufacturing Approach for OER Electrodes in PEM Water Electrolysis - Norbert Kazamer; Meike Tack; Mathias Spree; Martin Underberg; Ulrich Rost; Sven Reichenberger; Maximilian Cieluch; Haujin Salih; Florian Wirkert; Leonard Böhm; Jeffrey Roth; Varatharaja Nallathambi; et al. (Advanced Materials Interfaces)
Abstract The study introduces flexible and scalable manufacturing approach for electrodes utilizing boron‐doped silicon as conductive support for iridium nanoparticles, addressing the challenges of cost and scarcity associated wit noble catalysts for oxygen evolution reaction (OER). Colloidal Ir nanoparticles are synthesized via pulsed‐laser ablation (≈4–7 nm) and decorated on B‐doped Si (≈100 nm) through electrostatic adsorption. Titanium substrates are ultrasonically sprayed with Si:B – Ir and Ir nanoparticles with very low iridium loading of 12 wt.%. Crystalline Ir phases (Ir(111), Ir(200)) are observed and known to enhance the OER mechanism. Additionally, atom probe tomography confirms that the Si support particles contained 0.03‐0.5 at% of boron throughout the entire particle, while electrical permittivity and through‐plane measurements reveal a positive impact of B‐doped Si on the electrical conductivity of the nanocatalysts and of the ultralow‐loaded catalyst coated Ti substrates (0.12 mgIr cm−2), respectively. Rotating disk electrode results show pronounced oxidation peaks for decorated Ir nanoparticles. The Si:B‐Ir 4 nm catalyst exhibits the highest turonover frequency (2.62 s⁻¹) and a competitive electrochemical surface area (25 m2 gIr−1) compared to Si:B‐Ir 7 nm (0.96 s⁻¹; 37.5 m2 gIr−1) and Ir black (0.24 s⁻¹; 5 m2 gIr−1). The overall analysis of the parameters highlights a performant catalytic efficiency, through balancing activity and reaction kinetics effectively.